Development of a project tracking system for the Commission on Higher Education (CHED) funded projects - Tercia, Adelma C. (Technology Management Center, 2017)
The Commission on Higher Education (CHED) has been funding Research and Development and Extension (RDE) projects of Higher Education Institutions (HEIs) through the Research and Management Division (RMD). As a government agency, proper management of funds is imperative. Hence, the RMD is tasked to not only appropriate RDE funds to qualified recipients but also to ensure that project deliverables are completed as promised.